Familial hypercholesterolemia: current status of the problem, treatment, and prevention - S. A. Bliznyuk; M. G. Bubnova; M. V. Ezhov (Кардиоваскулярная терапия и профилактика, 2020)
Familial hypercholesterolemia is the most common hereditary disease characterized by an increase in low density lipoprotein cholesterol levels and the premature development of atherosclerosis-related cardiovascular diseases. Diagnosis and treatment of such patients are associated with certain difficulties. This review presents data on the prevalence of familial hypercholesterolemia, identification of patients with such a diagnosis, prevention of adverse cardiovascular events, and also discusses the appointment of lipid-lowering therapy.